Evidence for physical interaction between the zinc-finger transcription factors YY1 and Sp1. - Lee, J S (1993)
Two promoter elements are important for basal-level transcription, the TATA motif typically located 30 nucleotides upstream of the transcription initiation site and the initiator (Inr) element encompassing the start site. The mechanism of how Inr elements work is poorly understood, partly because very few proteins that bind to Inr elements have been identified and isolated. The recently cloned YY1 is such an Inr-binding protein. YY1 is able to direct transcription upon binding to its recognition sequence in vitro. The ability of YY1 to initiate transcription is augmented by the presence of a TATA motif or binding sites for transcription factor Sp1. To study the mechanism underlying the apparent functional cooperation between YY1 and Sp1, we explored the possibility of protein-protein interactions between these two transcription factors. We found that YY1 and Sp1 can form a physical complex. In addition, we identified domains within YY1 and Sp1 that mediate their interactions with each other. The physical interaction between YY1 and Sp1 may thus form the basis for the functional interplay observed previously.